Usman Awang Resistance to the Malay Humanity Facts in Uda and Dara Theatre Script - Salman Alfarisi (Tanjong Malim, 2021)
Usman Awang Resistance to the Malay Humanity Facts in Uda and Dara Theatre Script by Salman Alfarisi